Kualitas Layanan Digital dan Kepercayaan Pengguna Aplikasi BYOND by BSI: Peran Mediasi Persepsi Kepatuhan Syariah - Dewi Maslachah; Imam Sopingi; Peni Haryanti; Athi’ Hidayati (Kartika: Jurnal Studi Keislaman, 2026)
The development of Islamic digital banking in Indonesia has driven the increasing use of the BYOND by BSI application among university students. However, user trust in Islamic digital banking services is still influenced by many factors, including digital service quality and perceived sharia compliance. This study aims to examine the effect of digital service quality on user trust, with perceived sharia compliance as a mediating variable, in the BYOND by BSI application, study on gen Z  University students in jombang. The research strategy for this study was a quantitative survey. A total of 2,630 participants formed the study population, all students from the 2022–2025 intake at Hasyim Asy'ari University Tebuireng in Jombang who use the BYOND by BSI application. 100 participants were randomly selected using a quota sampling method, and the sample size was calculated using the Slovin formula with a 10% margin of error. The researchers used SmartPLS 4.0 software to run the SEM approach, which is based on PLS, to analyze the data. The study findings indicate that: (1) digital service quality has a positive and significant effect on user trust; (2) the quality of digital services has a positive and significant effect on the perception of sharia compliance; (3) the perception of sharia compliance has a positive and significant effect on user trust; and (4) the perception of sharia compliance is proven to partially mediate the effect of the quality of digital services on user trust in the BYOND by BSI application among Unhasy students.